Implementasi Metode Problem Solving Untuk Meningkatkan Hasil Belajar Materi Pendidikan Agama Islam Kelas VI UPTD SDN Dharma Tanjung 1 Kabupaten Sampang - Santoso, Agus; Purnamasari, Hetty; Hartati, Sulis Janu (STAI Muhammadiyah Paciran Lamongan, 2025)
This research aims to evaluate the effectiveness of implementing the Problem Solving method in improving the learning outcomes of Islamic Religious Education material for sixth-grade students at UPTD SDN Dharma Tanjung 1 Kabupaten Sampang. The study employs a classroom action research design, involving active participation of students and teachers over several learning cycles. The improvement in learning outcomes is measured through pre-test and post-test assessments, as well as observations of the learning process. The Problem Solving method is applied in the context of Islamic Religious Education to develop students' critical thinking skills and their ability to solve problems related to the material. Data collected will be analyzed using both quantitative and qualitative approaches to gain a comprehensive understanding of the impact of implementing the Problem Solving method on student learning outcomes. The results of this research are expected to make a positive contribution to the development of teaching methods at the elementary school level, particularly in the context of Islamic Religious Education. The practical implications of this research can serve as a guide for teachers in designing more effective and interactive learning strategies to enhance students' academic achievements in Islamic Religious Education.